Análise do Fundo Constitucional de Financiamento do Nordeste (FNE) sobre indicadores econômicos dos municípios durante o período de 2010 a 2020 - Monte, Kerlen Andrade do (2023)
The importance of evaluating and monitoring the execution of public policies for access to subsidized credit, specifically studies on the effects of Constitutional Financing Funds, has generated a scientific production that uses different econometric approaches in the evaluation of these types of Funds. The present work adopts the Generalized Propensity Score (GPS) econometric methodology to evaluate the volume of FNE credit contracted in the municipalities during the period from 2010 to 2020. By estimating the dose-response functions, developed by Imbens (2000) and Hirano and Imbens (2004), the results of credit participation aimed at women and legal entities reveal, in general, positive and growing effects on the variation of Average Income, GDP per capita and Salary Mass, suggesting heterogeneity in the effect of the FNE according to the magnitude of the volume of credit contracted, with the exception of Average Income, which has no effect when the resources were contracted by women. In the case of total transfers, positive impacts on average income, however, GDP per capita and wage mass were only observed in the last level of treatment. In summary, it can be inferred that FNE resources positively impact the economic and social indicators of municipalities with higher contracted amounts.